The Representation of Gay on Instagram (Semiotics Analysis of @Alpantuni Account) - Amrullah, Muhammad Ardhanie; Sokowati , Muria Endah (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2022)
Instagram is often used to resist negative stigma and discrimination for the homosexual because of its characteristics: dispersal, decentralized, and easily used. It encourages the homosexual to convey their ideas broadly, just the same as the straight people as the majority do. One of the examples is the @alpantuni account on Instagram. This account is trying to describe the life of becoming gay as the effect of a public understanding that being gay is a taboo. The account uses comic stripe with satire, Alpantuni as the main character of the comic stripe is a Muslim gay. I argue that this comic becomes the media to resist the public stigma of LGBT. Therefore, this paper will focus on the question of how the gay is represented in the @alpantuni account on Instagram, which performs the resistance against the stigma and discrimination. The paradigm of this research is interpretive with a hermeneutic approach and I use Roland Barthes’s semiotic analysis which divides two stages of interpretation. The stages are denotation and connotation with the myth which is attached to the research object. In the @alpantuni account on Instagram, 11 comic stripe posts could be analyzed. From the analysis, I found that the gays’ fear to express their thoughts and tend to be silent when their thoughts are considered to be erroneous. Those are caused by the inequity, discrimination and violence against the gays, and the majority promote democracy only for their own sake but are dogmatic to the thoughts of the gays. Thus, the story of the comic stripe containing the representation above is criticizing the current social conditions.